2010
DOI: 10.1155/2010/843729
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Gene Polymorphisms and Risk Assessment for Pulmonary Tuberculosis in Asian Indians

Abstract: Objective: Pulmonary tuberculosis (PTB) is a leading cause of morbidity and mortality. Macrophages play an important role in the immunopathogenesis of tuberculosis. Extracellular ATP induces macrophage bactericidal activity through activation of the purinergic P2X7 receptor. This case- control study assesses the association of −762 T/C, 1513A/C and 1729T/A P2X7 polymorphisms in patients with PTB and healthy controls to establish association if any with risk of developing the disease. Materials and methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 19 publications
(39 reference statements)
1
28
3
Order By: Relevance
“…We found that the -762 T allele is a risk factor for PTB in our study population. In contrast to our findings, Sambasivan et al (2010) found a significant difference between PTB patients and controls for the -762 C allele and reported that the C allele is a risk factor for PTB in the Asian Indian population. Xiao et al (2009) found that the -762T/C variant of P2X7 was not significantly associated with TB in the Chinese Han population.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the -762 T allele is a risk factor for PTB in our study population. In contrast to our findings, Sambasivan et al (2010) found a significant difference between PTB patients and controls for the -762 C allele and reported that the C allele is a risk factor for PTB in the Asian Indian population. Xiao et al (2009) found that the -762T/C variant of P2X7 was not significantly associated with TB in the Chinese Han population.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in their analysis, only males showed a signifi cant association between P2X7-762 T/C and TB. Our results were also similar to those observed in Indian populations, and are supported by a recent meta-analysis reporting subjects with the C allele at higher risk of developing TB [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, sequence changes in this region may affect the activity of P2X7 receptor expression and alters its ability to regulate macrophage activity which helps in controlling TB infection [22]. Additional to 762 polymorphism, 1513 T to C allele frequency in the P2X7 gene were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a protective effect against tuberculosis was associated with a P2X 7 receptor promoter polymorphism at position −762, but the 1513 A>C polymorphism discussed above did not show any significant association. Interestingly, Sambasivan et al [42] found an association between development of clinical tuberculosis and the presence of the −762C or 1729T allele but not the 1513C allele in an Indian cohort, while Xiao et al [43] did not find an association between either the 1513C allele or the −762C allele and the development of pulmonary tuberculosis in a Chinese Han cohort. Overall, though, a recent meta-analysis of P2X 7 receptor gene polymorphism association studies revealed a strong association between the 1513 A>C polymorphism and susceptibility to tuberculosis [44].…”
Section: The P2x7 Receptor and Intracellular Bacteriamentioning
confidence: 97%